PELATIHAN PENGENDALIAN ARUS SISA LISTRIK SESUAI PERSYARATAN UMUM INSTALASI LISTRIK DI DESA MELINGGIH PAYANGAN-GIANYAR - Ngurah Amrita, A.A.; Ibi Weking, A.; Ariastina, W. G.; Sukadarmika, G. (Buletin Udayana Mengabdi, 2017)
Power consumption is affected by population growth and community activities. In term of power consumptions, there are not many customer understand about the electricity component that must they pay monthly, whether the consumption really caused by the equipment or due to other things that cause energy kept unused and wasted unnecessarily. One of the causes of the increase in electrical power consumption is is the presence of residual current. The residual current needs to be controlled. It is probably caused by nonlinearities of equipment or due to electrical induction that can be harmful for human and environment. For example, Fires are often caused by the continuously presence of residual current. There is a standard for controlling residual current based on its implementation. If it is used for human, the safety system must be able to switch off when the residual current reaches 30 mA, while for electrical equipment, it is switched off if the residual current reaches 300 mA. Moreover, Control of the residual current must meet the General Requirements for Electrical Installations published by the National Standardization. Community Service Team from Electrical Department, Udayanan University organized socialization and training for community in Melinggih village. The result of those activities is the community able to understand the meaning of residual current including its effect and how to control the residual current